Diagnostic clues of organizing pneumonia: a case presentation - Rea, Gaetano; Pignatiello, Maria; Longobardi, Luca; Barbieri, Angela; Cappabianca, Salvatore; Valente, Tullio (Quantitative Imaging in Medicine and Surgery; Vol 7, No 1 (February 28, 2017): Quantitative Imaging in Medicine and Surgery, 2017)
Cryptogenic organizing pneumonia (COP) is currently an established clinicopathologic entity, expression of reparative reactions to acute lung injury and the resulting inflammation within the alveoli and distal bronchioles. COP continues to be included in the classification of IIP (Idiopathic Interstitial Pneumonias) because of its idiopathic nature and to date in the last European Respiratory Society (ERS)/American Thoracic Society (ATS) update statement of IIP and according to acute or subacute presentation, is included in section “acute or subacute IIPs” (1).